Perencanaan Jembatan Leho Kawasan Pesisir Kabupaten Karimun, Kepulauan Riau, dengan Struktur Jembatan Pelengkung (Arch Bridge) - Winarno, Adhyta Narendra; Pakpaham, Alfred Nobel; Tudjono, Sri; Nuroji, Nuroji (Jurnal Karya Teknik Sipil, 2013)
The Design of Leho Bridge in Karimun Coastal Area, Riau Islands, based on the needs of a transportation infrastructure that connecting the Old Town Area with Sei Bati Airport. This Bridge Structure is designed by using an Arch Bridge Structure considering that it’sfunction also as a monumental building.Based on the results of highway capacity analysis, the bridge’s width designed as 9,00 m with 2/2 UD type which the pavement is 7,00 m width and each of the pedestrians are 1,00 m width. Then the bridge’s  span is determined as 60,00 m, based on the gulf’s geometry and the boat’s traffic under the bridge. The Clearance below the bridge is affected by the highest water level and the boat’s heightwhich on this case is taken as 11,00 m.Through the design and the calculation with Load and Resistance Factor Design’s method we found the section of the arch rib is a box formed steel profile which size is 900.900.40.40 with the yield stress is 290 MPa. While the main beam using a box formed steel profile which size is 900.400.30.30 with the yield stress is 290 MPa. The foundation system is designed by using a group of sheet piles which the diameter is 60 cm as much as 24 piles on each abutments.